Wearable devices and ecological momentary assessment EMA in the workplace: A study protocol on work stress assessment - Giuseppina Dell’Aversana; Margherita Herold; Silvia Simbula; Isabella Ruina; Margherita Pillan; Massimo Miglioretti (PLoS ONE, 2026)
Work-related stress (WRS) remains a significant concern in occupational health. Despite its significance, measuring WRS presents methodological challenges. Advancements in real-time data collection methods offer new opportunities to enhance the accuracy of WRS assessment. This study proposes an innovative, participatory protocol for assessing WRS. The approach integrates subjective self-reported measures, collected through ecological momentary assessment (EMA), and physiological monitoring via wearable smartwatches. By combining time-contingent and event-contingent sampling, the methodology enables continuous tracking of stress responses throughout the workday, providing a more dynamic and context-sensitive understanding of workplace stress. A key objective of this research is to evaluate the feasibility and acceptability of implementing this protocol in real-world organizational settings. By incorporating participatory design principles, the methodology actively involves workers in the assessment process, ensuring that the tools and procedures are both effective and user-friendly. This participatory approach fosters engagement and compliance, ultimately improving the quality of collected data. This study contributes to developing more robust and ecologically valid stress assessment methods. Integrating real-time monitoring with self-reported data represents a promising direction for occupational health research, paving the way for more targeted and evidence-based interventions to mitigate workplace stress.